Groups : process and practice - Corey, Marianne Schneider, 1942-; Corey, Gerald; Corey, Cindy (Cindy C.); Brooks/Cole Publishing Company (Belmont, Calif. : Brooks/Cole, Cengage Learning, 2014)
'This book outlines the basic issues and key concepts of group process and shows how group leaders can apply these concepts in working with a variety of groups. In many ways this is a'how-to' book, but it is also a book about the'why' of group leadership...For the ninth edition, each chapter has been carefully reviewed and updated to present the current thinking and trends in practice.' --p. xxi
Introduction to group work -- Group counselor -- Ethical and legal issues in group counseling -- Theories and techniques of group counseling -- Forming a group -- Initial stage of a group -- Transition stage of a group -- Working stage of a group -- Final stage of a group -- Groups in school settings -- Groups in community settings -- Appendix.
Includes bibliographical references (p. 425-437) and indexes.
Keywords: Group psychotherapy; Group counseling; Group relations training; Group counseling; Group psychotherapy; Group relations training